Analisis Tanggung Jawab Negara dalam Pemenuhan Hak Pengasuhan bagi Anak Yatim Piatu Korban Pandemi Covid-19 - Prameswari, Sal Sabila Ayuning; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
Children's rights are one of the rights that must be fulfilled by the state specially Indonesia that declared as a legal state. One of the rights of children is the right to get proper care by family, community and state. However, the COVID-19 pandemic, which is a non-natural disaster, has made the number of orphans in Indonesia increase drastically at the same time.Thousands of millions of people died due to the COVID-19 pandemic and most of those who died were people of working age. This certainly has an impact on child care in Indonesia.The impact of the many productive people who die will certainly cause a butterfly effect, one of which is that children lose the caregivers who have been taking care of them. Children can also experience double grief if when they are abandoned by their parents, then the care shifts to their grandparents or uncles and then their family must be isolated or die suddenly due to COVID-19.The phenomenon of orphans due to the COVID-19 pandemic has consequences forcountries that have committed to protecting children's rights by ratifying the Convention on the Rights of the Child, one of which is to fulfill the rights of care for children abandoned by both parents in order to avoid neglect and ensure child's development well.The process of collecting data on children is one of the crucial steps in determining what kind of assistance and care scheme the orphans will receive. This requires cooperation and coordination between institutions and the community so that children get the best care.